2008
DOI: 10.1523/jneurosci.3402-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Is a Critical Modulator of CB2Cannabinoid Receptor Signaling during Neuropathic Pain

Abstract: Nerve injuries often lead to neuropathic pain syndrome. The mechanisms contributing to this syndrome involve local inflammatory responses, activation of glia cells, and changes in the plasticity of neuronal nociceptive pathways. Cannabinoid CB 2 receptors contribute to the local containment of neuropathic pain by modulating glial activation in response to nerve injury. Thus, neuropathic pain spreads in mice lacking CB 2 receptors beyond the site of nerve injury. To further investigate the mechanisms leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 43 publications
4
97
1
2
Order By: Relevance
“…At variance with our findings, previous studies on other experimental models of chronic inflammatory diseases, such as dermal fibrosis, atherosclerosis, and nerve injury, 10,12,25 have shown that enhanced monocyte infiltration is the predominant mechanism of the deleterious effects of CB2 −/− deletion. However, in these models, CB2 and CCR2 are weakly expressed by resident cells and predominantly exposed by infiltrating monocytes, whereas the opposite occurs within the glomeruli.…”
Section: The Observation That Cb2contrasting
confidence: 94%
“…At variance with our findings, previous studies on other experimental models of chronic inflammatory diseases, such as dermal fibrosis, atherosclerosis, and nerve injury, 10,12,25 have shown that enhanced monocyte infiltration is the predominant mechanism of the deleterious effects of CB2 −/− deletion. However, in these models, CB2 and CCR2 are weakly expressed by resident cells and predominantly exposed by infiltrating monocytes, whereas the opposite occurs within the glomeruli.…”
Section: The Observation That Cb2contrasting
confidence: 94%
“…We observed that IFN-␥ increased in both mixed glial culture and BV-2 cells (a microglial cell line) after JEV infection. Both glia and neurons could be the source of IFN-␥ early in infection (55). Although the ability of glial cells to be infected by flavivirus remains debatable, the studies by us and others clearly show that they are well activated during JE (25,56).…”
Section: Figmentioning
confidence: 92%
“…The time course of increased CB 2 R expression is similar to that of microglial activation, and the upregulation of CB 2 Rs also occurs in other diseases associated with microglial activation [32,33]. It was reported that microglial activation in the spinal cord after PNI is suppressed by administration of CB 2 R agonists and in mice overexpressing CB 2 Rs [26,34]. Furthermore, CB 2 R agonists decrease the level of the proinflammatory cytokine IL-1 in the spinal cord [27].…”
Section: Discussionmentioning
confidence: 76%